Artificial Intelligence for Enhancing the Effectiveness of Engineering Asset Management - Khaled El-Aktuti,; Ali Salem,; Othman Khalifa, (AlQalam Journal of Medical and Applied Sciences, 2025)
The integration of Artificial Intelligence (AI) into engineering asset management has the potential to significantly enhance decision-making processes, optimize resource allocation, and improve overall outcomes of industrial organizations. This paper explores the role of AI in engineering asset management, focusing on its applications, benefits, and challenges. The paper presents a simulation module that demonstrates the effectiveness of AI-driven strategies in managing engineering assets. Results from the simulation indicate that AI can lead to improved efficiency, reduced costs, and enhanced asset performance. The findings underscore the importance of adopting AI technologies in engineering asset management to meet the demands of modern complexity in managing assets/infrastructure in production or service organizations.